Religious counseling to improve psychological wellbeing of students - Ratnasari, Devi; Miskanik, Miskanik; Rahmaniah, Ayu (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2018)
This research tries to measure the effectiveness of religious counseling services on improving psychological well-being of students in SMK Nusantara Wisata Respati Jakarta. The research method used is quantitative research with quasi experimental type, and using purposive sampling technique. The subjects of the study 6 students who had low score in psychological well-being. The instrument used is the psychological well-being scale developed by Ryff. Based on result of data analysis by using sign test, known r = 0,009, so it can be concluded that the use of effective religious counseling can improve psychological well-being on the students of class XII SMK Nusantara Wisata Respati Jakarta. This confirms that religious counseling services are extremely helpful in correcting students psychological well-being. Enhanced psychological well-being is expected to optimize student performance so that its potential can be applied optimally